2010
DOI: 10.1007/s12402-010-0043-x
|View full text |Cite
|
Sign up to set email alerts
|

Self-perception of self-regulatory skills in children with attention-deficit/hyperactivity disorder aged 8–10 years

Abstract: Several studies have reported a characteristic "positive illusory bias" in the self-evaluation of children with ADHD. However, results are controversial. The aim of the present study was to investigate whether children with ADHD aged 8 to 10 years can rate their self-regulatory skills accurately when assessed with an age appropriate instrument. Twenty-seven children with ADHD and 27 matched normal control children completed the Self-rating Scale of Self-regulatory Function (SelfReg), a new rating scale that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…The opposite phenomenon has been observed in a subgroup of children with ADHD (Hoza et al 2002; Owens et al 2007; Rizzo et al 2010) and, to a lesser extent, in adults (Jiang and Johnston 2012; Knouse et al 2005): they show a characteristic overestimation of competence and/or performance, which is known as “positive illusory bias”. Children with ADHD show impaired error monitoring and a lack of characteristic post-error slowing in inhibitory response tasks (Schachar et al 2004).…”
Section: Neuropsychological Aspects In Ocd and Adhdmentioning
confidence: 97%
“…The opposite phenomenon has been observed in a subgroup of children with ADHD (Hoza et al 2002; Owens et al 2007; Rizzo et al 2010) and, to a lesser extent, in adults (Jiang and Johnston 2012; Knouse et al 2005): they show a characteristic overestimation of competence and/or performance, which is known as “positive illusory bias”. Children with ADHD show impaired error monitoring and a lack of characteristic post-error slowing in inhibitory response tasks (Schachar et al 2004).…”
Section: Neuropsychological Aspects In Ocd and Adhdmentioning
confidence: 97%
“…These metacognitive judgments are contemplated in the MASRL model proposed by Efklides (2011) and seem to be more accurately produced by children throughout the elementary school years (Schneider, 1998). Some authors argue (Rizzo, Steinhausen, & Drechsler, 2010) that children in this age group are capable of making accurate and differential judgments of their selfregulation processes and hence, be metacognitively active. Others posit that both children (from 8 years of age on) and adults are weak at determining good from bad performance because of their inaccurate confidence judgments (Allwood, Ask, & Granhag, 2005;Allwood, Innes-Ker, & Fredin, 2008).…”
Section: Children's Accuracy In Reporting Metacognitive Awarenessmentioning
confidence: 98%
“…Bares 2011). What's more, the literature has also suggested that children in this age group are also capable of making accurate and differential judgments regarding their self-regulation competencies when the evaluation method is appropriate for their age (Rizzo et al 2010).…”
Section: Introductionmentioning
confidence: 99%